Retrospective identification of bacterial depository revealed that Streptococcus iniae was responsible for some of the streptococcosis cases in cultured red tilapia in Malaysia since 2006 - Mohamad Ali, Siti Hawa; Mohammad Ridzuan, Mohd Syafiq; Abdullah, Siti Zahrah; Mansor, Nur Nazifah; Nawi, Mohd Firdaus; Saad, Mohd Zamri; Azmai, Mohammad Noor Amal (Universiti Putra Malaysia Press, 2020)
This paper reports the identification of Streptococcus iniae from a large collection of isolates previously identified as Streptococcus sp., Lactococcus lactis subsp. lactis or Leuconostoc sp. A total of 204 bacterial isolates recovered either from the brain, eye, or kidney of red tilapias in previous disease outbreaks and disease monitoring in Malaysia from 2006 to 2008 were used. PCR identification revealed that 34 (16.7%) of the isolates were confirmed as S. iniae. Our records showed that S. iniae-infected fish exhibited lethargy, exophthalmia, and erratic swimming patterns. Pathological lesions including generalised congestion of the internal organs, splenic infarction with soft and oedematous brain. Histopathological examination revealed multifocal encephalitis as one of the major findings. However, 44% and 26.5% of the tilapias from which S. iniae was isolated did not manifest any clinical sign and pathological lesion, respectively. This study revealed that S. iniae was responsible for streptococcosis in cultured red tilapia in Malaysia since 2006.